Machine learning on Kubernetes : build, deploy, and track your ML models on a containerized, sustainable machine learning platform /: build, deploy, and track your ML models on a containerized, sustainable machine learning platform. (2022) - Masood, Faisal; Brigoli, Ross
No abstract available